EFFECT OF NIMODIPINE AND DICLOFENAC IN EXPERIMENTALLY INDUCED CONVULSIONS USING ISONIAZID AND ELECTROCONVULSOMETER IN ANIMALS - RAJYALAKSHMI.N; SRIDEVI KALAVACHARLA; S.VIJAYA; M.PRASAD NAIDU (International Journal of Pharma and Bio Sciences, 2016)
Epilepsy is one of the common afflictions of human with a prevalence of approximately 1% of the total population. It is estimated that 50 Million person’s worldwide may have the disorder. Even though it was recognized as early as 2000 B.C. In the present study anticonvulsant activity of Nimodipine and combined effect of Nimodipine and Diclofenac was carried out against electrically induced & INH induced convulsions in rats and mice. To find out the difference between the Drugs (Control, Nimodipine and Nimodipine + Diclofenac) within each method (MES Method and Chemical Method), ANOVA was used. F ratio> 3.68 were considered to be significant. P-Value < 0.05 was considered to be significant. However, studies with other models of epilepsy and in combination with other Calcium channel blockers and COX inhibitors on experimental animals and human beings would be needed to substantiate the present work.